Persepsi Brand Familiarity dan Brand Trust Terhadap Brand Attachment (Survei terhadap Pelanggan Kopi Kulo di Indonesia - Zahfirah Nashshar (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
This study aims to determine the perception of brand familiarity and brand trust towards brand attachment among Kulo coffee customers on Instagram Kulogroup.id. The type of research used is descriptive and verification. The independent variables in this study are brand familiarity (X1) and brand trust (X2) and the dependent variable is brand attachment (Y). The research sample was taken using the incidental sampling method with a total of 410 respondents. The research instrument was tested using validity and reliability tests. The analysis technique applied is multiple linear regression analysis with the help of SPSS 24.0 for Windows software. The findings in this study indicate that the description of brand familiarity and brand trust perceptions of brand attachment is in the high category. Brand familiarity and brand trust have a positive and significant influence on brand attachment.